Virtual clinical excursions--general hospital for Potter and Perry : Fundamentals of nursing - Cooper, Kim D.; Potter, Patricia Ann (St. Louis, Mo. : Mosby Elsevier, 2009)
Virtual clinical excursions (VCE) is a workbook/CD-ROM package that accompanies many Elsevier nursing textbooks. The workbook guides users through Pacific View Regional Hospital, a virtual hospital setting, where one can learn communication, documentation, assessment, and safe medication administration. VCE offers a hands-on learning experience to help nurses improve both clinical judgement and critical thinking skills while interacting with a number of virtual patients.
"Pacific View Regional Hospital"--Cover
System requirements for accompanying CD-ROM: Windows Vista, XP, 2000; Mac OSX 10.2 or higher; 256 MB RAM
Keywords: Problems, exercises, etc